Alternative treatments for postharvest control of blue mold in ‘Fuji’ apples - Do Amarante C.V.T.* (2017)
This research was carried out to evaluate alternative treatments for postharvest control of blue mold (Penicillium expansum) in ‘Fuji’ apples. Fruit were punctured (diameter 2 mm and depth 4 mm) at the shoulders and then submitted to the following treatments (3-min immersion): control (distilled water); calcium hypochlorite (Frexus CH® 65%) at 0.08 g L-1; a proprietary isolate of Bacillus pumilus (Sonata®; aqueous suspension with 7 × 109 cfu mL-1) at 8 mL L-1; a proprietary extract of citrus biomass (Ecolife®; with bioflavonoids, ascorbic acid, citric phytoalexin, boron, organic acids and sugars) at 10 mL L-1; and potassium phosphite (Fitofos-K Plus®, with 40% P2O5 and 20% K2O) at 5 mL L-1. Twenty-four and 72 h after treatment, fruit were inoculated with P. expansum (0.1 mL, 1 × 106 conidia mL-1). Fruit were assessed for incidence and severity of decay over 9 days of shelf life at 22±2°C/70±5% RH. Fruit treatment with potassium phosphite provided the best control of blue mold over the shelf-life period, in fruit inoculated 24 and 72 h after treatment. B. pumilus was less effective at controlling decay than potassium phosphite, especially when fruit were inoculated 72 h after treatment. Treatments with calcium hypochlorite and citrus biomass were not effective at controlling decay. The results show that, among elicitors of decay resistance, only potassium phosphite was effective at controlling blue mold, with a limited effect of B. pumilus.